The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3109/15513815.2012.659414
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Adrenocortical Tissue: An Incidental Finding During Inguinal Surgery in Children

Abstract: Adrenal rests are usually unrecognized during operation, and the incidence of ectopic adrenal cortical tissue in pediatric patients during inguinal surgery procedures is unknown. We performed 3028 groin surgical explorations in 2680 patients aged 1 month to 17 years. Ectopic adrenal tissue was found in 69 inguinal operations (2.2%): 37 during 1.524 orchiopexy (2.4%), 23 during 1.115 herniectomy (2.0%), and 9 during 389 hydrocoela operation (2.3%). Statistically there were no significant differences among those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(28 reference statements)
0
5
1
Order By: Relevance
“…Ketata et al (14) found ectopic adrenal tissue in 1.66% (n = 31) out of 1862 patients who had inguinoscrotal surgery and adrenal medulla was not detected in any of the patients, while all had adrenal cortex. The general opinion is that the observation rate of medullar cells decreases toward zero the more distal the location of ectopic adrenal tissue is (12)(13)(14). However, we found that 1 of our 6 patients had adrenal cortex and adrenal medulla together.…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…Ketata et al (14) found ectopic adrenal tissue in 1.66% (n = 31) out of 1862 patients who had inguinoscrotal surgery and adrenal medulla was not detected in any of the patients, while all had adrenal cortex. The general opinion is that the observation rate of medullar cells decreases toward zero the more distal the location of ectopic adrenal tissue is (12)(13)(14). However, we found that 1 of our 6 patients had adrenal cortex and adrenal medulla together.…”
Section: Resultscontrasting
confidence: 51%
“…Similarly, by reviewing a large series, specific disorders or anomalies were not reported as any significant accompanying disease with ectopic adrenal tissues (12)(13)(14). Nevertheless, we did not detect any biochemical, hormonal (ACTH, testosterone, progesterone, and TSH), or hematologic abnormalities suggestive for ectopic adrenal tissue in our patients.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Ectopic adrenal tissue usually appears as an incidental finding during surgery. According to literature, despite its benign behavior, recommendation to remove ectopic adrenal tissue when discovered remains [8,7,13], since they are associated with hyperplasia and neoplastic change [1,5]. However, a routine search for them is not mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported ectopic cortical adrenal gland tissues in the inguinal region (spermatic cord, hernia sac, testis, epididymis, and ovary) with an overall incidence of 1.66-5.14% (Marchetti 1904;Nelson 1939;Gutowski and Gray 1979;Michowitz et al 1979;Mares et al 1980;Miersch et al 1989;Okur et al 1995;Ventura et al 1998;Lorenzo Romero et al 2000;Pérez García et al 2001;Oguzkurt et al 2002;Sullivan et al 2005;Mendez et al 2006;Vaos et al 2006;Iyengar and Pittman 2007;Ozel et al 2007;Ketata et al 2008;Dobanovacki et al 2013). The incidence of ectopic (intratesticular) adrenal gland tissue is quite high (42%) among patients with congenital adrenal gland hyperplasia (Avila et al 1999).…”
Section: Ectopic Adrenal Glandmentioning
confidence: 99%